Study on Decentralization of Forestry Management in Cameroon - André, Eloundou Jules (Challenging Issues on Environment and Earth Science Vol. 3, 2021)
At the end of the Rio de Janeiro Summit of June 1992 ,the forestry legislation has undergone a real revolution in Cameroon. As a result of the promulgation of Law n°94-01 on the 20th of January 1994, which established Forestry, Wildlife, and Fisheries Regulations, a great deal of innovation has occurred. This law is the compass for Cameroon's entire forestry programme. Among these innovations are the establishment of the Ministry of Environment and Forestry, as well as the establishment of council and community forests. Because sustainable development is a major concern to the Cameroon Government, the state has chosen to decentralise forestry management.